An improved approximation algorithm for the single machine total completion time scheduling problem with availability constraints - Sadfi, Cherif; Penz, Bernard; Rapine, Christophe; Błażewicz, Jacek; Formanowicz, Piotr (European journal of operational research, 2005)
In this paper, we study the single machine total completion scheduling problem subject to a period of maintenance. We propose an approximation algorithm to solve the problem with a worst case error bound of 3/17. Furthermore, an example is provided to show that the bound is tight. Computational experiments and an analysis are given afterwards.